Judicial precedent in the Algerian legal system - SERIKET, Loubna (Journal of Human Sciences, 2025)
The Algerian law was influenced by the French law- which precedes the Latin system – So the law arises essentially from legislation and the task of the judiciary is limited to applying the law in accordance with the principle of separation of powers, so Judicial precedents are not considered an official source of law according to Article 01 of the Algerian Civil Code, and the judicial ruling has relative authority is limited within the scope of similar cases, and the reason for this binding moral force of judicial precedents is the concern for consistency of rulings in the similar cases in a way that preserves their stability in order to ensure unification of the law within the state through unified interpretation. The Supreme Court and the Council of state are authorized to unify judicial jurisprudence in accordance with Article 179 of the Constitutional Amendment of 2020, and these two judicial bodies will not succeed in achieving this task effectively and truly except through their respect for the legal procedures that guarantee this.